Validity of Edupark Based Electronic Physics Module Hot Spring Padang Ganting for Senior High School - Yelda Sufetri; - Hamdi (Universitas Negeri Padang, 2020)
Currently, the use of Padang Ganting hot spring attraction as a place to learn or commonly called Edupark (educational park) is very good to do. Because the covid-19 outbreak the learning process went from face-to-face to online so that the use of learning devices such as module also switched into the form of electronic modules. In order for the learning process to continue well, an electronic module is needed integrated with Edupark. This type of research is Design Research by using plomp model. It has three stages namely 1) preliminary research (initial investigation), consisting of analysis of educators, learners, potential regions and materials, 2) prototyping phase (prototype phase) consisting of formative evaluation and 3) assessment phase. This research was limited only to the prototyping phase until the validity test using validation instruments with likert scale. There were several aspects of eligibility assessed by expert lecturers, namely aspects of presentation eligibility, appearance, material and language. The results of data from expert lecturers was then processed using descriptive data analysis. The result of processing data obtained from validators in the aspect of presentation eligibility got a value of 93,06 with a very valid category, a appearance eligibility aspect got a value of 90,79 with a very valid category, a material eligibility aspect got a value of 76,39 with a valid category and a language validation aspect got a value of 78,33 with a valid category. Validation results of the five aspects of the Edupark hot spring Padang Ganting electronic module from material eligibility aspects, appearance eligibility, presentation eligibility and language validity were very valid category based on validity criteria according to Arikunto with a value of 84,64